Spasticity Measurement Based on Tonic Stretch Reflex Threshold in Children with Cerebral Palsy Using the PediAnklebot - Germanotta, Marco; Taborri, Juri; Rossi, Stefano; Frascarelli, Flaminia; Palermo, Eduardo; Cappa, Paolo; Castelli, Enrico; Petrarca, Maurizio (Frontiers in Human Neuroscience, 2017)
Nowadays, objective measures are largely used to evaluate spasticity for overcoming the intrinsic limitations of the clinical scales. Among objective measures, Tonic Stretch Reflex Threshold (TSRT) seems the most promising. Previous studies demonstrated the validity and reliability of TSRT in the spasticity assessment at elbow and ankle level in adults. The purposes of this study were to assess: (i) the feasibility of TSRT to evaluate spasticity at the ankle joint in children with Cerebral Palsy (CP), and (ii) the correlation between objective measures and clinical scores. A mechatronic device, the pediAnklebot, was used to impose 50 passive stretches to the ankle of 10 children with CP and 3 healthy children to elicit muscles responses at 5 different velocities. Surface electromyography, angles and angular velocities were recorded to compute dynamic stretch reflex threshold; TSRT was computed with a linear regression through angles and angular velocities. TSRTs for the most affected side of children with CP were into the biomechanical range (95.7 ± 12.9° and 86.7 ± 17.4° for Medial and Lateral Gastrocnemius, and 75.9 ± 12.5° for Tibialis Anterior). In three patients, the stretch reflex was not elicited in the less affected side. TSRT were outside the biomechanical range in healthy children. However, no correlation was found between clinical scores and TSRT values. The ability of TSRT to discriminate between spastic and non-spastic muscles was here demonstrated, while no significant outcomes were found for the dorsiflexor.